Data from: Subarctic singers: Humpback whale (Megaptera novaeangliae) song structure and progression from an Icelandic feeding ground during winter - Magnúsdóttir, Edda E.; Lim, Rangyn (Zenodo, 2019)
Humpback whale songs associated with breeding behaviors are increasingly reported outside of traditional low latitude breeding grounds. Songs from a subarctic feeding ground during the winter were quantitatively characterized to investigate the structure and temporal changes of the songs at such an atypical location. Recordings were collected from 26. January to 12. March, 2011, using bottom mounted recorders. Humpback songs were detected on 91% of the recording days with peak singing activities during 9.–26. February. The majority of the recordings included multiple chorusing singers. The songs were characterized by a) common static themes which transitioned consistently to predictable themes, b) shifting themes which occurred less predictably and c) rare themes. A set median sequence was found for four different periods (sets) of recordings (approximately 1 week each). The set medians were highly similar and formed a single cluster indicating that the sequences of themes sung in this area belonged to a single cluster of songs despite of the variation caused by the shifting themes. These subarctic winter songs could, thus, represent a characteristic song type for this area which is comparable to extensively studied songs from traditional low latitude breeding grounds. An increase in the number of themes per sequence was observed throughout the recording period including minor changes in the application of themes in the songs; indicating a gradual song progression. The results confirm that continual singing of sophisticated songs occur during the breeding season in the subarctic. In addition to being a well-established summer feeding ground the study area appears to be an important overwintering site for humpback whales delaying or canceling their migration where males engage in active sexual displays, i.e. singing. Importantly, such singing activity on a shared feeding ground likely aids the cultural transmission of songs in the North Atlantic. Metadata - Phrases and total song detections The spread sheet ...